Frailty and sociodemographic and health factors, and social support network in the brazilian elderly: A longitudinal study - Jack Roberto Silva Fhon; Luípa Michele Silva Cabral; Suellen Borelli Lima Giacomini; Nayara Araújo dos Reis; Marcela Cristina Resende; Rosalina Aparecida Partezani Rodrigues (SciELO, 2021)
ABSTRACT Objective: To identify and analyze the sociodemographic and health factors and the social support network of the elderly associated with frailty in the assessments carried out between 2007/2008 and 2018. Methods: This is a longitudinal study with elderly people aged ≥65 years living in the community. The instruments used were those for Demographic Profile, the Mini Mental State Examination, the Functional Independence Measure, Lawton and Brody Scale, Geriatric Depression Scale, Minimum Relationship Map for the Elderly, and Edmonton Frail Scale. Descriptive analysis and linear regression were used, all tests with p < 0.05. Results: Of the 189 elderly in the study period (2007/2008-2018), most were 80 years old and over, with an average of 82.31 years old; they were women, with no partner, who lived with other family members and were retired. In the final analysis, regardless of age and sex, a decrease in functional independence, an increase in depressive symptoms, an increase in the number of self-reported illnesses, and an increase in the frailty score were observed. Conclusion: The factors that were associated with the increase in frailty of the elderly during the study period were age, female sex, and no partner. The health team, which includes nurses, shall be aware of changes and develop care plans to prevent or avoid their progression.